UK Consumers' Willingness to Pay for Eco-Friendly, Renewable Energy-Powered Agri-Food Systems - Gonzalez, Jorge Campos; Gadanakis, Yiorgos (My University, 2025)
Integrating anaerobic digestors (AD) and recirculating aquaculture systems (RAS) for sourcing King Prawns (KP) in UK agriculture is a promising farm diversification approach based on circular economy principles. RAS powered by AD renewable energy can boost farm Net Margins by up to 56% and 38% for arable and dairy farms, respectively, while promoting waste recycling and nutrient efficiency. KP is a healthy and mostly imported seafood, but there are concerns regarding environmental degradation and unsustainable practices abroad (e.g., mangrove deforestation). In addition, there is a lack of understanding of consumer preferences regarding UK-grown KP. We investigate the willingness to pay (WTP) for UK-sourced KP under standard and environmentally friendly systems integrating AD. We collected 282 responses on, among others, consumer demographics, purchasing preferences, and origin. We apply Weber's law to build price increments for our WTP analysis. The results illustrate a higher WTP for UK-grown prawns under both systems and the likelihood of switching to a ‘UK option’. Under standard practices, 27.3% of respondents were willing to pay an additional £0.51–£1.05, considering a £5 baseline price (approx. the retail price for a 150 g unit). Regarding ‘environmentally friendly practices’, 26.87% were willing to pay £0.51–£1.05, and 19.38% would pay £1.05–£1.60. When considering a switch from usual prawns purchases to the UK option, 45.18% were somewhat likely under both production scenarios. Still, the highly likely group doubled to 29.82% for a system powered by AD energy, highlighting strong consumer preference for sustainability. The principles of a circular economy and domestic production positively influence consumer choice. The WTP findings suggest a premium market price for agri-food businesses while supporting the integration of RAS and AD. This potential transformation opens avenues for innovative practices that satisfy the demand for healthy diets and support the transition towards more sustainable food systems
Keywords: Sustainable Entrepreneurship; Willingnes to Pay; King Prawns; Recirculating Aquaculture Systems; Agriculture; Anaerobic Digestor